Elements of Financial Statements: Usefulness in Investment Decisions - Brazendra Nath Roy (Institute of Accounting Research and Novation (IARN), 2023)
Elements of financial statements are the main sources of financial information of a corporation to the external users. The main objective of the study is to measure the usefulness of the components of the financial statements in investment decisions to investors. A well designed questionnaire regarding the usefulness of the components in the decision making was provided among the investors living in the northern part of Bangladesh. Only 74 investors provided their opinion through online platform. Then the data is analyzed using descriptive statistics, cornbach alpha, correlation and measures of association. After analyzing the result of the study, it is found that financial statements have a significant influence on several investment decisions of the investors. The result of study will encourage investors to use the information contained in the financial statements for fruitful investment decision. It is tried to discover the real scenario of usefulness of the financial statements to the investors as if the study covers only a limited area of Bangladesh